Performance Analysis and Alternative Treatments at the Intersection of Jl. Gusti Situt Mahmud-Parit Pangeran in Pontianak - Nisa, Marfiratun; Mukti, Elsa Tri; Mayuni, Siti (Jurnal Teknik Sipil, 2024)
Increased traffic activity can result in congestion, delays, or accidents at unsignalized intersections. This study assesses the performance of the three-arm unsignalized intersection at Jl. Gusti Situt Mahmud-Parit Pangeran, Pontianak, under current conditions and a 5-year forecast. The analysis employs the Pedoman Kapasitas Jalan Indonesia (PKJI) 2023 and VISSIM software, with data gathered during peak hours on Mondays from 17:00 to 18:00. In the present scenario, PKJI 2023 indicates a degree of saturation (DJ) of 0.95, a delay of 17.08 seconds, and a Level of Service (LOS) C, while VISSIM shows a delay of 21.10 seconds and LOS C. For the 5-year forecast, PKJI 2023 predicts a DJ of 1.07, a delay of 22.76 seconds, and LOS C, whereas VISSIM anticipates a delay of 21.10 seconds and LOS D. The most effective solution to enhance intersection performance includes widening significant roads, adding lanes, and incorporating medians, which would achieve an LOS A, thereby effectively mitigating congestion and delays for both current and projected conditions.